2014
DOI: 10.1001/jama.2014.15095
|View full text |Cite
|
Sign up to set email alerts
|

Extent, Location, and Clinical Significance of Non–Infarct-Related Coronary Artery Disease Among Patients With ST-Elevation Myocardial Infarction

Abstract: In a retrospective pooled analysis of 8 clinical trials, obstructive non-IRA disease was common among patients presenting with STEMI, and was associated with a modest statistically significant increase in 30-day mortality. These findings require confirmation in prospectively designed studies, but raise questions about the appropriateness and timing of non-IRA revascularization in patients with STEMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
145
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(157 citation statements)
references
References 32 publications
5
145
1
6
Order By: Relevance
“…Our study further extends these conclusions to patients with STEMI who underwent PCI in nIRA CTO as shown in another meta‐analysis of contemporary RCTs in patients with STEMI with multivessel CAD 7. The idea that patients with acute STEMI and concurrent nIRA CTO would demonstrate clinical benefit from CTO PCI was generated from the apparent 2‐fold increased mortality and morbidity rates among patients with STEMI and multivessel CAD and CTO 4, 5, 21. Even among patients without STEMI, increased mortality has been attributed to the presence of CTOs in nIRAs 3, 6.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Our study further extends these conclusions to patients with STEMI who underwent PCI in nIRA CTO as shown in another meta‐analysis of contemporary RCTs in patients with STEMI with multivessel CAD 7. The idea that patients with acute STEMI and concurrent nIRA CTO would demonstrate clinical benefit from CTO PCI was generated from the apparent 2‐fold increased mortality and morbidity rates among patients with STEMI and multivessel CAD and CTO 4, 5, 21. Even among patients without STEMI, increased mortality has been attributed to the presence of CTOs in nIRAs 3, 6.…”
Section: Discussionsupporting
confidence: 69%
“…The treatment of choice for STEMI is percutaneous coronary intervention (PCI) to restore blood flow to the occluded infarct‐related artery 1, 2. Approximately 50% of patients presenting with STEMI are found to have multivessel coronary artery disease (CAD) with concomitant stenotic lesions in noninfarct‐related arteries (nIRAs) and ≈12% to 13% are found to have a chronic total occlusion (CTO) in an nIRA 3, 4. Prior studies have shown that the presence of a CTO in an nIRA in patients with STEMI is linked to an increase in short‐ and long‐term mortality 4, 5.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Between April 2013 and July 2015, we recruited 42 patients (62±9 years) from routine coronary angiography waiting lists, in 2 distinct groups (Figure 1): Patients with obstructive coronary stenoses (n=32): defined by either a coronary artery stenosis >50% on quantitative coronary angiography15 or fractional flow reserve ≤0.8 16. These patients had typical anginal symptoms and multiple risk factors, or known obstructive coronary artery stenoses awaiting percutaneous coronary intervention.…”
Section: Methodsmentioning
confidence: 99%
“…1-3 A substantial number of STEMI patients are also found to have significant stenosis in non-culprit vessels during primary PCI. [4][5][6][7] The optimal strategy for the management of these lesions has not been well established. 1,2,[8][9][10] Two recent randomized controlled trials have demonstrated improved outcomes with multivessel revascularization in STEMI patients with multivessel disease.…”
Section: Introductionmentioning
confidence: 99%